Antibacterial activity of haemolymph extracted from coccinella septempunctata against escherichia coli: a preliminary study - Zulkipli, Husna; Musa, Nadia Nisha; Hishammuddin, Diya Batrisyia; Mokhtar, Nur Afiqah Marissa (2025)
This study investigated the antibacterial activity of haemolymph extracted from Coccinella septempunctata against bacteria Escherichia coli. The rising issue of antibiotic resistance has encouraged the search for alternative natural antibacterial sources, including from insect haemolymph, which contains antimicrobial peptides (AMPs). In this study, haemolymph was extracted and tested using the agar well diffusion method on nutrient agar inoculated with E. coli. Four (4) treatment groups were prepared by mixing haemolymph (H) with buffer A (BA) (pH 6), B (BB) (pH 6.5), C (BC) (pH 5) and distilled water (DW) respectively. The results showed that haemolymph combined with BB resulted in the largest inhibition zone (5 mm), followed by BA and BC (4 mm), while combination with DW showed the smallest inhibition zone (2 mm). These findings suggest that haemolymph from C. septempunctata potentially exhibits antibacterial properties against E. coli, with buffer composition affecting its efficacy. Thus, the results highlight the potential of haemolymph derived from insects as a natural antimicrobial agent for future study.